Topography of Lipid Droplet-Associated Proteins: Insights from Freeze-Fracture Replica Immunogold Labeling. (5th December 2010) - Robenek, Horst; Buers, Insa; Robenek, Mirko J.; Hofnagel, Oliver; Ruebel, Anneke; Troyer, David; Severs, Nicholas J.
Abstract : Lipid droplets are not merely storage depots for superfluous intracellular lipids in times of hyperlipidemic stress, but metabolically active organelles involved in cellular homeostasis. Our concepts on the metabolic functions of lipid droplets have come from studies on lipid droplet-associated proteins. This realization has made the study of proteins, such as PAT family proteins, caveolins, and several others that are targeted to lipid droplets, an intriguing and rapidly developing area of intensive inquiry. Our existing understanding of the structure, protein organization, and biogenesis of the lipid droplet has relied heavily on microscopical techniques that lack resolution and the ability to preserve native cellular and protein composition. Freeze-fracture replica immunogold labeling overcomes these disadvantages and can be used to define at high resolution the precise location of lipid droplet-associated proteins. In this paper illustrative examples of how freeze-fracture immunocytochemistry has contributed to our understanding of the spatial organization in the membrane plane and function of PAT family proteins and caveolin-1 are presented. By revisiting the lipid droplet with freeze-fracture immunocytochemistry, new perspectives have emerged which challenge prevailing concepts of lipid droplet biology and may hopefully provide a timely impulse for many ongoing studies.